Pengaruh Kompetensi Guru PAUD Dalam Meningkatkan Daya Tarik Pembelajaran Di Era New Normal - Siti Nurul Aprida; Nurul Fauziah; Abd Rosyid (UIN Sultan Maulana Hasanudin Banten, 2022)
Teacher competence is a professional standard for educators in understanding learning materials, as well as matters relating to the learning process. The purpose of this study was to determine the effect of PAUD teacher competence in increasing the attractiveness of learning in the New Normal Era. This study uses a quantitative method in which the data processing uses simple linear regression. The population in this study were 50 teachers in Bantul Regency, Yogyakarta. Methods of data collection using a questionnaire technique and also interviews. To test the analysis using the F regression test and the coefficient of determination. Based on the results obtained that there is a strong influence between understanding teacher competence and increasing the attractiveness of learning in this new normal era. This is based on the acquisition of the percentage of the influence of 63.7%. So that there is a link between the knowledge of teacher competence and increasing children's interest in learning.